Diagnosis and outcome in nonhydropic fetal pleural effusions. (29th August 2018) - Wellesley, Diana; Howe, David T.
Abstract: Objective: To determine the outcome of all pregnancies with nonhydropic fetal pleural effusions in the Wessex region. Method: Data were extracted from the Wessex congenital anomaly database for the years 1994‐2015 inclusive. Results: Sixty‐two fetuses and babies were identified giving a total prevalence of 1:9500. Eight fetuses had bilateral effusions with additional, nonhydrops anomalies, and 54 had isolated effusions. Of the isolated cases, 36 presented before 24‐week gestation: 12 were unilateral and 24 bilateral. All of the unilateral effusions resolved before or soon after birth with no other diagnosis but of the bilateral cases, four (17%) had a trisomy and three (13%) a genetic or syndrome diagnosis. Eighteen isolated cases presented after 24‐week gestation, six were unilateral of which one had trisomy 21 (17%), and three (50%) Noonan's or another lymphoedema syndrome. Twelve were bilateral: One had trisomy 21, one an unbalanced translocation (17%), three had Noonan's or another lymphoedema syndrome, and two an unspecified syndrome (42%) at birth. Conclusion: These data suggest that a chromosomal microarray should be offered to all fetuses presenting with a pleural effusion in the absence of hydrops, and Noonan's syndrome testing should be considered for those that develop after 24 weeks. Aim: To determine the outcome of all pregnancies with nonhydropic fetal pleural effusions in the Wessex region from 1994–2015.